Erysipelas of the face. What you need to know an ophthalmologist? - E.E. Grishina; Syhova Т.Е. (РМЖ "Клиническая офтальмология")
E.E. Grishina, T.E. Sukhova M.F. Vladimirsky Moscow Regional Research and Clinical Institute (MONIKI), Moscow, Russian Federation Abstract Erysipelas is an infectious disease characterized by fever, intoxication and inflammatory cellulitis-like lesions of the skin, subcutaneous tissue and superficial lymphatic vessels. The disease is caused by group A streptococci (Streptococcus pyogenes). Given the well-developed lymphatic network on the face surface, we can state that the inflammation caused by streptococcus, starting with the tissues of the eyelid, spreads rapidly, within a few hours, to at least half the face, and more often to the whole face and neck area. Thus, the diagnosis of isolated erysipelas of the eyelid is not valid. The article describes the clinical picture of the facial erysipelas and examples of the erroneous diagnosis of erysipelas, leading to a delay in initiating adequate treatment. Thus, the development of isolated erysipelas of the eyelids is impossible. Erysipelas is an infectious disease, and it should be treated by an infectious disease specialist in a hospital. If there is no positive dynamics for 3–5 days, it is necessary to consider the possibility of complications, or an erroneous diagnosis of erysipelas. Examination by an ophthalmologist will help to exclude eyeball complications of the erysipelas. Key words: erysipelas, facial erysipelas, eye, infection, group A streptococci. For citation: Grishina E.E., Sukhova T.E. Facial erysipelas. What does an ophthalmologist need to know? RMJ “Clinical ophthalmology”. 2018;2:155–160.